Behavioral Pattern of Rent Distribution of Subsidized Fertilizer) - Sastra, Eka; Damanhuri, Didin; Achzani, Noer Azam; Aerani, Ahmad (Advances in Social Sciences Research Journal, 2021)
The subsidized fertilizer policy is the government's effort to increase agricultural production and productivity in general. However, in the distribution process, there are still various distribution problems that lead to rent-seeking behavior. The purpose of this research is to describe the behavior of rent-seekers in the distribution of subsidized fertilizers. The research method used is focus group discussion (FGD) involving various stakeholders including (1) government, (2) academics, (3) associations, (4) farmer groups, (5) government-owned enterprises, and fertilizer distributors. The results showed that there had been a pattern of rent-seekers distributing subsidized fertilizers to farmers. The behavior of these rent-seekers includes fertilizer prices exceeding the Highest Economic Price (HET), transaction costs, fertilizer distribution that is not on target until there is a shortage of fertilizer. The government needs to develop a new strategy to optimize the distribution of subsidized fertilizers to farmers. The strategy is to change the subsidy policy to a direct subsidy to farmers. Furthermore, the government needs to optimize investment in the agricultural sector in the form of technology, human resources, electricity, and road infrastructure.